Контурно-токовая модель поиска затонувших объектов - Рябенький, В.М.; Чудайкин, И.И.; Таргунакова, Ю.Д. (Технічна електродинаміка, 2012)
The authors introduce mathematical model which defines connection between base sources magnetic field and measured magnetic field of a sank objects in a coordinate system. Independent current loops are acts as the base sources and creates information network at the water area bottom. Mathematical model result examples with different test sets are also provided.